Financial Contagion and Good Corporate Governance on Bank Companies Performance in Indonesian Stock Exchange - Sugiyanto, Sugiyanto; Tukiyat, Tukiyat (Universitas Pamulang, 2021)
This study aims to examine the effect of fianancial contagion and good corporate governance on company performance of banks company listed on Indonesia Stock Company. Corporate governance is measured using the number of independent commissioners, frequency of board meetings, and attendance at board meetings. This study has two dependent variables, namely market performance as measured by Price Earning Ratio (PER) and operational performance as measured by return on equity (ROE). The analysis method used is multiple regression models with two dependent variables. The results showed that the contagion effect had a positive influence on the company's PER performance but did not have an effect on the company's ROE performance. Meanwhile, corporate governance through the board of directors' meeting is able to have an influence on ROE performance but not on PER. This shows that when there is a domino effect from another country it will have an influence on share prices in the market.